Sangamon and Pre-Sangamon Interglaciations in the Hudson Bay Lowlands of Manitoba - Dredge, Lynda; Morgan, Alan; Nielsen, Erik (Géographie physique et Quaternaire, 1990)
ABSTRACTThe manuscript documents voluminous new and published stratigraphie and paléontologie data from a region unique in North America, and possibly the world, in that it has abundant natural exposures recording a long and consistent succession of Quaternary tills and fossiliferous intertill sediments. Two major non-glacial intervals have been recognized under tills. Various non-glacial sediments have been correlated using their stratigraphie position, pollen analysis, and beetle assemblages, and are found to be equivalent to the Missinaibi Formation in Ontario. Non-finite high pressure radiocarbon dates, and aspartic acid ratios on wood suggest that the uppermost and most prevalent interval is of Sangamonian age. The Sangamonian record begins and ends with cool intervals, separated by a warmer period when climates were similar to or slightly warmer than present, and when the northern treeline was near its present position. The interval began with a high glacioisostatic sea, which regressed to levels below present Hudson Bay datum. The Sundance paleosol and silt beds below the Amery till relate to an earlier interglaciation characterized by cool tundra conditions. As an analogue for predicting future global change, the record preserved in the Hudson Bay Lowlands is second to none: additional intensive research is strongly recommended.